2010
DOI: 10.1007/s00423-010-0685-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound elastography—a noninvasive diagnostic procedure for evaluating dominant thyroid nodules

Abstract: Purpose Ultrasound elastography (USE) is a newly developed technique for the evaluation of tissue stiffness. It is known that malignancies often show a low-strain value. So far, only limited data for thyroid nodules is available. Methods This study included 309 prospective evaluated patients with dominant, nontoxic thyroid nodules. All patients were referred to surgery. USE was performed preoperatively. Three measuring groups were formed: hard (< 0.15), intermediate (0.16-0.3), and soft (> 0.31). The measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 22 publications
2
87
1
5
Order By: Relevance
“…Some groups analyzed the diagnostic value of the absolute A value for strain, as displayed by the machine when computing strain ratio [47,77]. However, this approach is highly disputable, since, as discussed above, RTE machines only compute the relative strain in an area and not the absolute strain.…”
Section: Limitations and Causes Of False Results For Srmentioning
confidence: 99%
“…Some groups analyzed the diagnostic value of the absolute A value for strain, as displayed by the machine when computing strain ratio [47,77]. However, this approach is highly disputable, since, as discussed above, RTE machines only compute the relative strain in an area and not the absolute strain.…”
Section: Limitations and Causes Of False Results For Srmentioning
confidence: 99%
“…The efficacy of USE in distinguishing benign from malignant thyroid nodules varies widely, ranging from 34% to 100% in different studies (Lyshchik et al, 2005;Rubaltelli et al, 2009;Rago et al, 2010;Vorlander et al, 2010;Cakir et al, 2011;Lippolis et al, 2011). USE may be viewed as a form of palpation by means of US and, as such, the examination may be influenced by operator's experience.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, elastography is usually performed as an extension of convencional US and not as an independent test (Kwak and Kim, 2014). Vorländer et al (2010), confirmed the possibility of measuring the increased stiffness in Hashimoto disease by using magnetic resonance elastography and in other study was reported the possible possible usefullness of ARFI to confirm the presence of Graves disease and chronic autoimmune thyroiditis (Zaleska-Dorobisz et al, 2014).…”
Section: Primary Applications Of Elastographymentioning
confidence: 88%